Upacara Abhumi Sudha Dalam Rangkaian Upacara Maligia Lajur (Perspektif Pendidikan Agama Hindu) - Ida Ayu Putu Cintya Giri Purwati; Ni Made Sukerni; I Made Arsa Wiguna (Kamaya: Jurnal Ilmu Agama, 2019)
The procession was held in front of the Sanggar Tawang as a symbolic cleansing of the entire Payadnyan area by means of Pendeman which was tied with Tri Datu yarn, Bila wood twings, Tri Datu yarn, flour and Panca Datu, and Medori gold jewel rings. The issues to be discussed include; (1) The Abhumi Sudha ceremony procession in the Maligia Lajur ceremony series? (2) The function of the Abhumi Sudha ceremony in the maligia lajur ceremony series? (3) The values of Hindu religious education contained in the Abhumi Sudha ceremony in the Maligia Lajur ceremony series?. This study aims to determine; (1) The Abhumi Sudha ceremony procession in the Maligia Lajur ceremony series. (2) The function of the Abhumi Sudha ceremony series. (3) The values of Hindu religious education in the Abhumi Sudha ceremony in the Maligia Lajur ceremony. Are religious theories, functional structural theories, and value theory. Data collection methods applied are metthods of observation, interviews, literature studies, and documentation. The data that has been collected is analysis method with steps of reduction, data presentation, and conclusion drawing. The results showed (1) The procession of the Abhumi Sudha ceremony began with preparing several types of offerings or offerings which would be used for the ceremony of the Abhumi Sudha such as Pendeman Panca Datu, flour, Bila wood twigs, Tri Datu thread, and gold Medori jewel rings. In the peak of this procession begins with bathing the oxen, and given clothes and jewelry like humans. It was given and cleansing ceremony so that the ox improved its purity to become Dang Hyang Nandini. After that the Abhumi Sudha ceremony was carried out by walking form the southwest to the northeast which was called Akasa Sudha then from northwest to southeast which was called Pertiwi Sudha. The composition of flour, the yarn that is stretched and the giving of gold reproduction of Medori gems as a symbol of the cleansing ceremony has been completed. (2) The Abhumi Sudha ceremony has several functions such as spiritual function, social function, and preservation function. (3) value of hindu religious education in Abhumi Sudha ceremony; Sradha value, Tri Kaya Parisudha value, Tri Rna value, devational teacher and aesthetic value.